Peningkatan Pemahaman Siswa di Madrasah Ibtidaiyah pada Mata Pelajaran Bahasa Inggris dengan Menerapkan Model Pembelajaran Flipped classroom: Flipped classroom; English Skill; Classroom Action Research; Student Engagement - Andiyani, Nurul Shifa; Nasihudin; Mahmud, Muhammad Rifqi (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2025)
This research aims to improve students' English skills through the implementation of the Flipped classroom model in class VB of MI Miftahul Huda Bandung. The study addresses students' low understanding of English material due to the use of conventional teaching methods and limited class time. The research uses Classroom Action Research (CAR) with the Kemmis and McTaggart model, conducted over four cycles, each involving planning, implementation, observation, and reflection. The subjects were 21 students in class VB. Data was collected through observation, interviews, documentation, and written tests. The results showed an improvement in students' comprehension from the pre-cycle to cycle IV. In the pre-cycle, the average score was 57 with a 27% completion rate. After applying the Flipped classroom model, the scores gradually improved: cycle I (63, 39% completion), cycle II (67, 52% completion), cycle III (72, 62% completion), and cycle IV (79, 86% completion). Student activity also increased from 57% in cycle I to 85% in cycle IV, while teacher activity remained at 100%. The findings suggest that the Flipped classroom model effectively enhances student engagement and learning outcomes. It allows students to access material outside class, learn at their own pace, and promotes greater learning independence. This model is highly relevant in primary schools with diverse student learning abilities.